Internet as a Meeting Place for Spouses: Homogamy, Assortative Mating and Online Dating in Contemporary Italy - Arosio, Laura (European Scientific Journal, ESJ, 2023)
This article studies the places where spouses met for the first time in Italy. The focus is on online settings in the most recent marriage cohorts (2000-2009 and 2010-2016). The aim is to investigate trends over time in the use of the Internet as a meeting place and to explore whether Internet dating can affect the rules of assortative mating and homogamy. Information about first marriages is analyzed to focus on highly engaged relationships. A quantitative approach is used and bivariate and multivariate analyses are conducted. The data used for the analyses come from the national representative survey "Family, social subjects and life cycle" carried out by the Italian National Institute of Statistics (Istat) in 2016 and made available in 2020. The results allow a preliminary quantification of the phenomenon and document an increase in online dating in Italy (from 0.4 percent of spouses who first met online in the marriage cohort 2000-2009 to 2.5 percent in the cohort 2010-2016). The data support the idea that online contexts show homogamy paths not different from those that characterize offline dating venues. Meeting an online partner doesn’t seem to imply heterogamy.